Telephone Problem-Solving Treatment Improves Sleep Quality in Service Members With Combat-Related Mild Traumatic Brain Injury: Results From a Randomized Clinical Trial. Issue 2 (March 2016) - Vuletic, S.; Bell, K. R.; Jain, S.; Bush, N.; Temkin, N.; Fann, J. R.; Stanfill, K. E.; Dikmen, S.; Brockway, J. A.; He, F.; Ernstrom, K.; Raman, R.; et al.
Abstract : Objective: Evaluate sleep quality, its correlates, and the effect of telephone-based problem-solving treatment (PST) in active duty postdeployment service members with mild traumatic brain injury (mTBI) Setting: Randomized clinical trial. Participants: Active duty service members with combat-related mTBI. Study design: Education-only (EO) and PST groups ( N = 178 each) received printed study materials and 12 educational brochures. The PST group additionally received up to 12 PST telephone calls addressing participant-selected issues. Outcomes were evaluated postintervention (6 months) and at 12 months. Main Measure: Pittsburgh Sleep Quality Index. Results: Sleep quality was manifestly poor in both groups at baseline (Pittsburgh Sleep Quality Index = 12.5 ± 4). Overall sleep quality was significantly different between the PST and EO groups at 6 months ( P = .003) but not at 12 months. Longitudinally, PST significantly improved sleep quality at 6 months ( P = .001) but not over the follow-up. Low sleep quality was associated with concussion symptoms, pain, depression, and posttraumatic stress disorder at all time points ( P < .0001). Conclusions: Sleep disorders, common in postdeployment service members with mTBI, are strongly associated with the presence of pain, posttraumatic stress disorder, and depression. Telephone-based PST may be an effective therapeutic approach for reducing sleep disorders in this population. Research should focus on maintenance of treatment gains.